2004
DOI: 10.1103/physrevb.70.214503
|View full text |Cite
|
Sign up to set email alerts
|

Elastic forward scattering in the cuprate superconducting state

Abstract: We investigate the effect of elastic forward scattering on the ARPES spectrum of the cuprate superconductors. In the normal state, small angle scattering from out-of-plane impurities is thought to broaden the ARPES spectral response with minimal effect on the resistivity or the superconducting transition temperature Tc. Here we explore how such forward scattering affects the ARPES spectrum in the d-wave superconducting state. Away from the nodal direction, the one-electron impurity scattering rate is found to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 27 publications
(29 reference statements)
3
59
0
Order By: Relevance
“…The shape of Σ(k, ω) are also modified by the impurity scatterings. [18] The VHS peak may be substantially suppressed by the coupling to boson spectrum and impurity scatterings. One should perform the selfconsistent calculations to see their effects without misleading conclusion.…”
Section: Preliminary Analysismentioning
confidence: 99%
“…The shape of Σ(k, ω) are also modified by the impurity scatterings. [18] The VHS peak may be substantially suppressed by the coupling to boson spectrum and impurity scatterings. One should perform the selfconsistent calculations to see their effects without misleading conclusion.…”
Section: Preliminary Analysismentioning
confidence: 99%
“…Impurities away from the CuO planes induce a relatively smooth potential, so the effective scattering range should be long. As a result, the out-of-plane impurities will induce mainly forward scattering which will strongly reduce the life-time of the anti-nodal quasi-particles without increasing the residual resistivity [19]. Optical conductivity measurements using the same kind of samples found that the Fe substitution reduces the superfluid density of the samples [20], this is expected to reduce T c since according to the Uemura relation T c ∝ n s .…”
mentioning
confidence: 99%
“…In the high-T c cuprate compounds it is believed that scatterers within the CuO 2 planes act as unitary scatterers and thus should have little influence on the Andreev bound states. However, it has been recognized recently that scatterers sitting between the CuO 2 planes are poorly screened and act as Born scatterers 17,18,19 . These impurities are thus expected to have a dominating influence on the broadening of the Andreev bound states.…”
Section: Introductionmentioning
confidence: 99%